Orthopaedic surgery resident consultations at a level I trauma center. Issue 1 (January 2019) - Snoap, Tyler; Walbridge, Joseph; Albright, Patrick; Weistroffer, Joseph; Kenter, Keith
Abstract : Background: The responsibilities of an on-call orthopaedic surgery resident has been minimally described in the literature. The most common diagnoses, procedures, and surgical cases that occur during an on-call shift would be of interest to an incoming resident. This study was designed to provide insight as to the knowledge and skills necessary to be a competent orthopaedic surgery resident on call. Methods: An electronic databank was created for the on-call residents to prospectively log inpatient and emergency department consultations at a level I trauma center over a 3-month period. Pertinent information was gathered about each consultation such as the diagnosis, treatment required in the emergency department or formal operative suite, type of anesthetic used to complete a reduction or procedure if necessary, duration of consultation, and more. Results: Over 500 consults were recorded during the collection period. The top three most common diagnoses included distal radial and/or distal ulnar fracture (8.2%), hand laceration (8.0%), and compression, burst, transverse process, or fracture dislocation of the spine (5.7%). The top three most common procedures or reductions performed in the emergency department included closed reduction of a fracture (38.9%), irrigation and debridement (24.0%), and closed reduction of a fracture dislocation or isolated dislocation (15.7%). Conclusions: This is the first study to evaluate the most common diagnoses and procedures encountered by orthopaedic residents on call at a level I trauma center. The results of the study can be utilized by orthopaedic program directors and department chairs, residents in training, and medical students.